Electrochemical Sensor for Hydrogen Peroxide Based on Prussian Blue Electrochemically Deposited at the TiO2-ZrO2–Doped Carbon Nanotube Glassy Carbon-Modified Electrode - Fernández, Lenys; Alvarez-Paguay, Jocelyne; González, Gema; Uribe, Rafael; Bolaños-Mendez, Diego; Piñeiros, José Luis; Celi, Luis; Espinoza-Montero, Patricio J. (Frontiers in Chemistry, 2022)
In this investigation, a hydrogen peroxide (H2O2) electrochemical sensor was evaluated. Prussian blue (PB) was electrodeposited at a glassy carbon (GC) electrode modified with titanium dioxide– and zirconia-doped functionalized carbon nanotubes (TiO2.ZrO2-fCNTs), obtaining the PB/TiO2.ZrO2-fCNTs/GC-modified electrode. The morphology and structure of the nanostructured material TiO2.ZrO2-fCNTs was characterized by transmission electron microscopy, the specific surface area was determined via Brunauer–Emmett–Teller, X-ray diffraction, thermogravimetric analysis, and Fourier transform infrared spectroscopy. The electrochemical properties were studied by cyclic voltammetry and chronoamperometry. Titania-zirconia nanoparticles (5.0 ± 2.0 nm) with an amorphous structure were directly synthesized on the fCNT walls, aged during periods of 20 days, obtaining a well-dispersed distribution with a high surface area. The results indicated that the TiO2.ZrO2-fCNT–nanostructured material exhibits good electrochemical properties and could be tunable by enhancing the modification conditions and method of synthesis. Covering of the nanotubes with TiO2-ZrO2 nanoparticles is one of the main factors that affected immobilization and sensitivity of the electrochemical biosensor. The electrode modified with TiO2-ZrO2 nanoparticles with the 20-day aging time was superior regarding its reversibility, electric communication, and high sensitivity and improves the immobilization of the PB at the electrode. The fabricated sensor was used in the detection of H2O2 in whey milk samples, presenting a linear relationship from 100 to 1,000 μmol L−1 between H2O2 concentration and the peak current, with a quantification limit (LQ) of 59.78 μmol L−1 and a detection limit (LD) of 17.93 μmol L−1.